The Volatility of the Parallel Exchange Rate in Venezuela 2005-2015 - Castillo Paredes, Laura Daniela; Ramoni Perazzi, Josefa (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The parallel exchange rate is one of the most important economic variables for decision making in Venezuela. With the purpose of analyzing the exchange rate considering its inherent characteristics, excess kurtosis, persistence and asymmetry, a theoretical synthesis of the main stochastic volatility models is made and a set of models is estimated. The results show that the model that best explains its behavior is an EGARCH (1.1); it captures the asymmetric effect of stochastic perturbations on the series. Negative shocks (depreciation of the parallel exchange rate) increase the volatility while positive shocks (appreciation of the parallel exchange rate) seem not to exert any effect.